2010
DOI: 10.1152/ajpgi.00258.2010
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal lipid nutrition alters early intestinal development and programs the response to experimental colitis in young adult rats

Abstract: The long-chain polyunsaturated n-6 and n-3 fatty acids are essential nutrients in membrane biogenesis and regulate gene expression via their eicosanoid metabolites. We investigated whether the n-6 and n-3 fatty acid supply as determined by maternal diet alters colonic phospholipid fatty acids, intestinal morphology, and epithelial barrier permeability during milk feeding with lasting effect on mucosal responsiveness to dinitrobenzene sulfonic acid (DNBS)-induced colitis in young adulthood. Female rats were fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 44 publications
5
45
0
1
Order By: Relevance
“…Appropriate fixation of samples is a key to study both the histopathological damage and visualization of target molecules in tissues by H&E and immunostaining, respectively. Histological scoring of tissues should be performed by experienced individuals who are blinded to the experimental conditions, using fixed criteria set by the individual investigator 11,17 . Myeloperoxidase (MPO) serves as a good marker of inflammation, tissue injury and neutrophil infiltration into gastrointestinal tissues 11 .…”
Section: Collecting Tissues and Assessing Histological Damage In Dnbsmentioning
confidence: 99%
“…Appropriate fixation of samples is a key to study both the histopathological damage and visualization of target molecules in tissues by H&E and immunostaining, respectively. Histological scoring of tissues should be performed by experienced individuals who are blinded to the experimental conditions, using fixed criteria set by the individual investigator 11,17 . Myeloperoxidase (MPO) serves as a good marker of inflammation, tissue injury and neutrophil infiltration into gastrointestinal tissues 11 .…”
Section: Collecting Tissues and Assessing Histological Damage In Dnbsmentioning
confidence: 99%
“…These observations showed that ARA via metabolism of LA was a key determinant in fat mass and globally underlined that LA/LNA ratios during perinatal period could have important programming effect on body composition (Ailhaud et al, 2006). Further proofs of evidence of lipids being involved in programming other functions were obtained in 2010 in animal models (rodents) by two research groups (Innis et al, 2010;Oosting et al, 2010). These results were obtained on non-dairy lipids but paved the way for further investigations on 'dairy lipid structure and programming' conducted just after by Oosting et al (2011Oosting et al ( , 2012Oosting et al ( , 2014.…”
Section: Introductionmentioning
confidence: 90%
“…The n-6/n-3 ratio in key factor of perinatal nutrition and programming Innis et al (2010) proposed that the increasing incidence of inflammatory bowel disease observed in Western countries over the last decades could be linked to dietary factors including perinatal lipid nutrition. They set the hypothesis that perinatal lipid nutrition affects, directly or indirectly through microbiota modulation, the epithelial barrier function and development, immune system and inflammatory response.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our group had shown that excessive dietary n-3 PUFA (8 and 18% energy fish oil) fed to rat dams during gestation and lactation primed offspring to display impaired intestinal barrier development evident by reduced intestinal crypt length associated with altered permeability and heightened susceptibility to DNBS-colitis at 3 months of age. 20 The objective of this study was to determine if altered intestinal microbial ecosystem is a pre-determining factor that leads to increased susceptibility to colitis in offspring of rat dams fed a diet rich in n-3 PUFA, like fish oil, compared to a diet rich in n-6 PUFA, like safflower oil. We examined the intestinal luminal microbes as well as mucosal immune cell populations of their newborn offspring.…”
Section: Introductionmentioning
confidence: 99%